National models for the integration of migrants: what impact on PISA results? - Lauwerier, Thibaut; Akkari, Abdeljalil (Swiss Journal of Educational Research, 2020)
There is an age-old debate between those who believe that intercultural education is conceptually superior to multicultural education and those who believe that there are no significant differences between these two models of cultural diversity management. In this paper, we first analyse the arguments used in this debate. In a second step, we will use data from the PISA survey to compare the results of countries that have adopted interculturalism (France, Spain, Switzerland) with those that adopted multiculturalism (Canada, United States, United Kingdom). The comparison will focus on the outcomes of students from diverse backgrounds (first and second generation immigrant students). This comparison will explore the possible links between integration models (interculturalism or multiculturalism) and school performance to see if a model actually makes a difference on these issues.